Sui generis no more? The ECB's second decade. Issue 3 (2nd April 2020) - Chang, Michele
ABSTRACT: At the start of Economic and Monetary Union (EMU), the ECB's sui generis nature as one of the most independent central banks of an entity lacking political union evoked concerns that it would be both too constrained (limited mandate) and enjoy too much discretion (limited ex-post accountability) in comparison to central banks like the US Federal Reserve. Were these concerns justified? Using a principal-agent framework, this contribution contrasts the ECB with the Federal Reserve in their reactions to the global financial crisis and how the available accountability mechanisms were used. Early concerns that the ECB would pursue only price stability at the expense of other economic objectives were exaggerated, though criticism about its accountability proved prescient.